Thermo-Hydro-Mechanical Numerical Analysis of Energy Pile in Saturated Clay. Issue 7 (October 2021) - Chen, Nan; Liu, Jiqiang; Xiong, Yonglin; Zheng, Rongyue
Abstract: In order to study the mechanical properties of energy piles under long-term heat injection-heat extraction cycle loading conditions, the influence of temperature on the mechanical properties of foundation soils needs to be considered. The subroutine of an elastic-plastic constitutive model of soil considering the influence of temperature is developed in Abaqus. Finally, the changes of additional pile top displacement, lateral friction resistance and axial force of energy pile under long-term heat injection-pumping cyclic loading under different loads and different soil parameters under the same load are discussed. The results show that: (1) The soil around the pile is subjected to plastic deformation due to the expansion and contraction of the pile. The higher the load on the pile top is, the greater the additional temperature settlement generated at the pile top is. (2) Under 0.5PU load, the increase of OCR, swelling index or permeability coefficient of foundation soil will cause the decrease of additional settlement of pile top. And the additional side friction and axial force, plastic parameters or soil permeability coefficient increases will produce greater additional side friction and axial force. This study has certain significance for the long-term use of energy piles.